Development of Gen Z International Economics E-Book Based on Problem Based Learning to Improve Soft Skills - Zuhri Saputra Hutabarat; Heni Pratiwi (Jurnal Pendidikan Edutama, 2026)
The purpose of this study in developing the Gen Z International Economics E-Book provides easy and practical access in studying international economic trade material in the growth and development of generation Z. with this e-book the material is presented briefly, clearly, concisely, accompanied by various evaluation questions designed to improve soft skills. This research method uses R & D-based Development and Problem Based Learning by applying the Four-D model (Define, Design, Develop and Disseminate), this method is applied to economic education students. The results of this study: 1) Become a means of improving economic literacy, especially Gen Z students, and 2) Construct the material developed in the e-book between the relationship between theory and practice so that Gen Z students understand better in real life. Through this study it is concluded that the use of this E-Book is useful in improving the soft skills of Gen Z students in college.